A dose based approach for evaluation of inter-observer variations in target delineation. (September 2017) - Kristensen, Ingrid; Nilsson, Kristina; Agrup, Måns; Belfrage, Karin; Embring, Anna; Haugen, Hedda; Svärd, Anna-Maja; Knöös, Tommy; Nilsson, Per
Highlights: Uses consensus volume to visualise inter-observer variation in dosimetric terms. Using DVHs in absolute volume adds information to evaluate uniformity. DVH for consensus volume adds information hidden in concordance indices. Report together with other measures. Completes the evaluation of delineation studies. Abstract: Background and purpose: Substantial inter-observer variations in target delineation have been presented previously. Target delineation for paediatric cases is difficult due to the small number of children, the variation in paediatric targets, the number of study protocols, and the individual patient's specific needs and demands. Uncertainties in target delineation might lead to under-dosage or over-dosage. The aim of this work is to apply the concept of a consensus volume and good quality treatment plans to visualise and quantify inter-observer target delineation variations in dosimetric terms in addition to conventional geometrically based volume concordance indices. Material and methods: Two paediatric cases were used to demonstrate the potential of adding dose metrics when evaluating target delineation diversity; Hodgkin's disease (case 1) and rhabdomyosarcoma of the parotid gland (case 2). The variability in target delineation (PTV delineations) between six centres was quantified using the generalised conformity index, CIgen, generated for volume overlap. The STAPLE algorithm, as implemented in CERR, was used for both cases to derive a consensus volumes. STAPLE is a probabilistic estimate of the true volume generated from all observers. Dose distributions created by each centre for the original target volumes were then applied to this consensus volume. Results: A considerable variation in target segmentation was seen in both cases. For case 1 the variation was 374–960 cm 3 (average 669 cm 3 ) and for case 2; 65–126 cm 3 (average 109 cm 3 ). CIgen were 0.53 and 0.70, respectively. The DVHs in absolute volume displayed for the delineated target volume as well as for the consensus volume adds information on both "compliant" target volumes as well as outliers which are hidden with just the use of concordance indices. Conclusions: The DVHs in absolute volume add valuable and easily understood information to various indices for evaluating uniformity in target delineation.